Combining metric and vector space data mining methods for screening CFTR rescuers in cystic fibrosis - Coelho, Inês Cristina Ferreira (2018)
Tese de mestrado, Bioinformática e Biologia Computacional (Bioinformática) Universidade de Lisboa, Faculdade de Ciências, 2017